Measuring the costs of African animal trypanosomosis, the potential benefits of control and returns to research - Kristjanson, Patricia M.; Swallow, B.M.; Rowlands, G.J.; Kruska, Russell L.; Leeuw, P.N. de (Elsevier, 1999)
This paper addresses issues surrounding measurment of the potential productivity gains from new livestock technologies and the returns to international livestock research. The approach, applicable to many livestock production constraints and technologies, uses geographic information systems (GIS) to spatially link a biophysical herd simulation model with an economic surplus model. The particular problem examined is trypanosomiasis in cattle in Africa, and the potential research product is a multi-component vaccine. The results indicate that the potential benefits of improved trypanosomiasis control, in terms of meat and milk productivity alone, are $700 million per year in Africa. The disease now costs livestock producers and consumers an estimated $1340 million annually, without including indirect livestock benefits such as manure and traction. Given an adoption period of 12 years, a maximum adoption rate of 30 percent, a discount rate of 5 percent, and a 30 percent probability of the research being successful within 10 years, the net present value of the vaccine research is estimated to be at least $288 million, with an internal rate of return of 33 percent, and a benefit/cost ratio of 34.1.